DRAGOLJUB JOVANOVIĆ'S MESSAGES ABOUT WORK AND BLUE COLLAR – WHITE SLAVES IN SECOND-HAND CAPITALISM - Stanojević, Marko (Political Review, 2023)
Throughout its history, Serbia has had a large number of important intellectuals, great people in the spiritual and moral sense who left a great mark on the world and Serbian cultural and scientific heritage. However, rarely were these people recognized and their opinion respected in the time in which they worked, and even more rarely were their messages and teachings the guiding thread of those times. The first Serb doctor at the Sorbonne, who received his doctorate in the field of work, invested all his intellectual and political energy in efforts to show Serbs how they should organize work, what optimal work should be based on, how to direct social development and how to a society of social justice is being organized in which work will be the most important value. The values ​​that the proletariat fought for, work, solidarity, social justice, in the new planetary order, have almost disappeared. The working class, which was the ruling class at certain moments, has become a class/layer that is scattered into pieces and that is slowly disappearing, changing its form and its essence – from blue – collar workers to white slaves! The intention of this essay is to, using the analysis of Dragoljub's texts on work, and then a comparison with the present time, point out, first of all, the basic messages of the doctor of labor from the Sorbonne, which concern precisely the issue of work, then the state of the working class (blue – collar workers) today and on the basis of that analysis and on the basis of the messages of Dragoljub's search for a more certain future of blue – collar workers.
Keywords: Dragoljub Jovanović; concept of work; blue collar workers; working class; transition